Disseminated pulmonary actinomycosis with hepatic injury: a misleading form mimicking a polymetastatic picture - Rakotoson, J L; Andrianasolo, R; Rakotomizao, J R; Rakotoharivelo, H; Andrianarisoa, A C F (Revue de pneumologie clinique, 2012)
Thoracic actinomycosis, caused by bacteria of the Actinomyces genus, is a rare infection, with poor prognosis if untreated, whose clinical and radiological picture is misleading, which can simulate a tumoral or tuberculous disease. This is a case of generalised pseudotumoral pulmonary actinomycosis in a non-smoking, non-drinking 48-year-old man, who for one month has been presenting a cough with haemoptoic sputum, dyspnoea associated with fever and a deterioration in general condition. The clinical examination discovered weight loss, diffuse crackling rales and multiple dental caries. Biologically, he presented an inflammatory syndrome. The radiological imaging and lung and liver CT-scans discovered a peripheral lung mass right side associated with multiple nodular cannon-ball opacities, multiple liver lesions of metastatic appearance. The bacteriological examination of the bronchoalveolar lavage fluid (Gram stain and culture) and the transparietal biopsy of the lung mass confirmed the presence of Actinomyces. Progress under treatment with 10 million international units of parenteral penicillin G daily over a period of six weeks substituted by three grams of amoxicillin/clavulanic acid daily over a period of 12 months and following an oral preparatory procedure was favourable. The thoraco-abdominal scan carried out three months after the treatment showed that the lesions had completely disappeared. Our case illustrates the diagnostic difficulty of actinomycosis particularly faced with a picture of multiple lung and liver metastasis. Hence, the importance of a histological and bacteriological examination of samples. The prognosis of this complaint is generally good following well-managed, prolonged treatment; and the prognosis peculiar to disseminated forms is less certain.